Biocontrol of Cercospora leaf spot in sugar beet by a novel Bacillus velezensis KT27 strain: Enhanced antifungal activity and growth promotion in laboratory and field conditions - Agnieszka Wita; Wojciech Białas; Katarzyna Czaczyk; Agnieszka Drożdżyńska; Łukasz Sobiech; Monika Grzanka; Jakub Danielewicz; Ewa Jajor; Joanna Horoszkiewicz; Roman Marecik (PLoS ONE, 2025)
Diseases in crops are a major contributor to yield reduction and economic losses. Cercospora leaf spot (CLS), caused by Cercospora beticola, is among the most severe diseases affecting sugar beet and other crops. The increasing resistance of C. beticola to conventional chemical fungicides, along with their excessive application, exacerbates environmental pollution. This study investigates the antagonistic activity of a newly isolated strain, Bacillus velezensis KT27, against Cercospora beticola, Rhizoctonia cerealis, and Fusarium oxysporum under laboratory conditions. The bacterium’s ability to produce lipopeptides (surfactin, iturin, and fengycin) and solubilize phosphorus, potassium, and zinc was also assessed. In vitro assays revealed that B. velezensis KT27 effectively inhibited C. beticola growth (60.2%), though it exhibited lower antagonistic activity against R. cerealis (22.5%) and F. oxysporum (15.5%). The elimination of bacterial biomass by centrifugation and the use of sterile supernatant reduced antifungal activity by more than 3.5-fold for all tested fungi, highlighting the importance of direct bacterial interactions. Notably, the antagonistic effect of B. velezensis KT27 against C. beticola significantly increased when bacterial cultures were supplemented with thermally inactivated fungal biomass of C. beticola especially R. cerealis. Field experiments demonstrated the high efficacy of B. velezensis KT27 biological control agent, particularly when induced by R. cerealis. The level of CLS protection achieved with the bacterial treatment was only 9.1% lower than that obtained using a combination of three chemical fungicides. Additionally, the biocontrol agent positively influenced sugar beet growth, leading to a root yield increase of up to 15.2% compared to the untreated control. These findings highlight the potential of B. velezensis KT27 as an effective and environmentally sustainable biocontrol agent against CLS in sugar beet cultivation.